Biogasoline synthesis through fluid catalytic cracking of rubber seed oil - effect of catalyst - Nurul Syafiqah, Rosli (2017)
Biogasoline is an alternative solution towards reducing global fossil fuel consumptions. Currently, there are numerous researches focusing on different feedstock of vegetable oils used to synthesis biodiesel is performed but less is focusing on biogasoline production. Therefore, the new approach to synthesis biogasoline is implemented in this study. Rubber seed oil (RSO) is studied as a feedstock to synthesis biogasoline through fluid catalytic cracking process using ZSM-5 as a catalyst. It is feasible to produce biofuels rich in different fractions such as gasoline, kerosene and diesel via catalytic cracking technique from edible and inedible oils and also plant extracts. In this study, Dean Stark method is applied as experimental set up. The amount of ZSM-5 is varied from 0.5 grams to 2.0 grams at 250℃. The experiment is run at 1 minute, 5 minute and 10 minute and the sample collected will be analyzed using Gas Chromatography Mass Spectrometry. The molecular formula of hydrocarbon obtained from the analysis of sample will be compared with standard gasoline range which is